Dramaturgi Pengemis Badut Karakter Di Kota Pekanbaru - Ramadhani, Yola; Susanti, Rina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The phenomenon of the presence of beggars clown characters has been often found in society, one of which is in the city of Pekanbaru. This study aims to determine the background of the beggar clown charater’s rational choice in choosing the job and aims to determine the front stage dan back stage of beggar clown character’s life. The type of this research is field research and uses a qualitative approach with a purposive sampling techniques. Data collection techniques use observation, interviews and documentation. Data analysis in this study used rational choice theory by James Coleman and dramaturgical theory by Erving Goffman. The result of this study indicate that their rational choice become a beggar clown character because they get income every day, there are factors involved and their identities are covered. There are differences shown on the front stage and the back stage. Entertaining behavior, looking friendly and compassionate towards children and looking for compassion are the front appearance of the beggar clown character. The beggar clown character’s back stage, they are not looking for a sympathy and the necessities of their life are fulfilled.